DIGITAL LEISURE AMONG YOUNG FEMALE STUDENTS OF COLLEGES - Muhammad Fayyaz Khokhar; Professor Liu Bangfan; Tayyaba Zia (International Journal of Contemporary Issues in Social Sciences, 2024)
Youth of present age leisure activities experience is transformed from the previous generations used to enjoy before the digital boom. We analyzed the data collected by 400 students from two different colleges adopting a constructive approach to study how virtual age has innovated their leisure-based activities, how it affected their psychological health, and to what extent family bonding was affected by them. The extensive exposure to technology has created a non-homogeneous experience among family members, but it also controls the user’s mind. Increasingly sophisticated digital devices and applications are being used for home-based digital leisure. More research is required to examine how digital leisure impacts other aspects of people’s lives.